Thai Study with The Thai Community Study - Toadithep, Tanit (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This article aims to review the educational guidelines of the Thai community. The results of this study have shown that the creation of knowledge in Thai studies is influenced by Western methods of thinking both methodologically and educationally by foreign scholars. The methods of community education in Thai studies can be classified into mainstream historical studies. Education based on local history Education of the Bureau of Community Culture Education under a social context modern culture and politics and proposes a counter-educational approach as a link between people, communities, localities and the global system.